A New Finite Time Convergence Condition for Super‐Twisting Observer Based on Lyapunov Analysis. Issue 3 (23rd August 2014) - Mu, Chaoxu; Sun, Changyin
Abstract A new convergence condition is proposed for the super‐twisting sliding mode observer in this paper, where Lyapunov stability analysis is used as the main method to get the new convergence condition. The super‐twisting sliding mode observer is designed to obtain unknown system states of the second order nonlinear system with bounded uncertainties and disturbances. By involving a quadratic Lyapunov function, the Lyapunov approach is applied to the stability analysis of the super‐twisting observer, from which a new convergence condition is obtained to guarantee the finite time convergence of the observer. Simulation results of a pendulum and a rigid manipulator are included to demonstrate the effectiveness of the new convergence condition.